IMPROVING THE STUDENTSâ READING COMPREHENSION ABILITY THROUGH SQ3R STRATEGY - Sabarun, Sabarun (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2012)
The study is aimed at improving the studentsâ reading comprehension ability in reading English class using SQ3R strategy, which refers to a reading technique covering a five step system developed by Francis P Robinson. Each of the steps stands for Survey, Question, Read, Recite, and Review. The study employed Classroom Action Research design. The subjects of the study were four of third semester students of the English Department of Palangka Raya State Islamic College of 2009/ 2010 academic year. The study was carried out in two cycles by following the four steps of action research: planning, implementing, observing, and reflecting. Each cycle consisted of one meeting focusing pre-reading, whilst reading and post reading. The data of the study are taken from the results of observation checklists, field notes, and the studentsâ reading score. The result of the study showed that SQ3R strategy could improve the studentsâ reading comprehension ability. It could be seen from the improvement of the studentsâ reading scores. The students were actively involved in reading class and they were highly motivated to attend the SQ3R reading class.Keywords: improving, SQ3R strategy, reading comprehension ability